Pengaruh Tingkat Kematangan Emosi, Fasilitas Belajar, Motivasi Terhadap Kreatifitas Belajar Mahasiswa Universitas Jambi - Robi Hendra; Boy Indrayana; Zuhri Saputra Hutabarat; Adellia Adellia; Muhammad Rifqi; Irma Sulistyawati; Dyfa Maharani Andalusia; Putri Nurhidayati; Ryan Ilhamsyah (Universitas Batanghari Jambi, 2023)
The background of this research is to see the effect of the level of emotional maturity of students in learning, the facilities and infrastructure in the university environment and to see the effect of student learning motivation on the quality and creativity of Jambi University students. This study also aims to determine whether emotional maturity, learning environment, and learning motivation affect the creativity of Jambi University students in learning. The approach in this research is to use a quantitative approach. The method used is the survey method in the form of a closed questionnaire with a total population of 500 active students at Jambi University with a sample of 50% of the total population, namely 250 students. The distribution of this research questionnaire was via Google Form, with data processing and analysis using the help of SPSS 26.0 and SMART PLS 25.0 software programs. From the results of the measurement hypotheses obtained from: (1) Mean, (2) STDEV, (3) T-Values, and (4) P-Values, with a P-Value of 0.000 <0.05 then H0 is rejected, then the maturity level is significant Emotions, Learning Facilities, Learning Motivation have a positive effect on the Learning Creativity of Jambi University Students